Structural, magnetic and microwave absorption properties of natural iron sand. Issue 1 (April 2021) - Handoko, E; Sugihartono, I; Marpaung, M A; Budi, S; Fahdiran, R; Jalil, Z; Alaydrus, M
Abstract: This paper presents the development and characterization of the natural iron sand as a microwave absorber. To develop a new microwave absorbing paints in the 7–13 GHz range, the iron sand sample was prepared through the mechanical milling process and characterized with X-ray diffraction (XRD), scanning electron microscopy (SEM), Permagraph and vector network analyzer (VNA). The reflection loss (RL) was calculated and simulated for different thicknesses of the material using the complex permittivity and permeability and found the broadband characteristics with minimum absorption. The results indicated that the natural iron sand is beneficial as potential candidates for military applications.